Penyusunan Rencana Persediaan dan Perkiraan Kebutuhan Kapasitas Jangka Panjang di PT.X - Nita Marikena; Yuli Setiawannie (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Production capacity planning is part of operations management that is realistic and applicable, so estimates of production capacity originating from forecasting consumer demand for these products must be known in advance so that companies can use resources effectively, in terms of quantity, time, and costs used for the production process. PT. X is a company that produces products in two groups, namely Product Group-I and Product Group-II. Product Group-I consists of two types of products, namely Product A and Product B, while Product Group-II consists of Product C and Product D. The Company is still experiencing difficulties in meeting consumer demand for these two product groups for the long term. This study aims to determine the total estimated consumer demand for two product groups within one year and the number of production machines needed to optimize the production process. Based on the results of calculations and analysis, the total estimated demand for Product Group-I for 12 months is 2216 units with a production time of 1520 hours. Meanwhile, the total estimated demand for Product Group-II for 12 months is 2,896 units with a production time of 1,709 hours. To meet consumer demand, PT. X must provide 2 units of production machines that are operated in parallel.